Forests and floods: drowning in fiction or thriving on facts? [Chinese] (CIFOR and FAO Regional Office for Asia and the Pacific, 2005)
There is a tendency to blame all natural disasters on human abuse of the natural environment. This is no more evident than in the case of devastating floods and landslides that affect the personal and economic fortunes of millions of people every year. Each disaster is followed by a predictable response. Upland farmers and loggers are blamed for clearing and degrading forests. In many people’s minds the use and abuse of forests in upland watersheds represents the main cause of massive lowland fl oods. This booklet explores the scientific evidence linking floods and forests. It reveals that much of what is ingrained in people’s minds cannot be substantiated by science and is often little more than myth or is patently incorrect. Such conventional wisdom has often led decision-makers to implement misguided policies that adversely affect the livelihoods of millions of people living in upland areas. Forests and floods distinguishes fact from fiction and recommends alternative approaches for effective watershed and floodplain management and so constructively contribute to the development of sound watershed and river-basin management and improved flood-mitigation policies.